Interictal burden in migraine patients at the outset of CGRP monoclonal antibody prevention - Christian Lampl; Elizabeth Seng; Maurice Vincent; William R. Lenderking; Margaret Hoyt; Lucinda Hetherington; Mary Kate Ladd; Karen Malley; Jun Chen; Lars Viktrup (The Journal of Headache and Pain, 2024)
Abstract Background The total burden of migraine includes not only the episodes with headache pain but extends throughout the interictal periods. Interictal symptoms and associated psychological responses may profoundly impact well-being and drive treatment-seeking behavior. Methods A cross-sectional online survey was conducted with participants aged ≥ 18 years, 250 with episodic migraine (EM) and 250 with chronic migraine (CM), having ≥ 4 monthly migraine headache days. All were naïve to galcanezumab or began ≤ 6 months before survey completion. The study evaluated factors associated with the Migraine Interictal Burden Scale (MIBS-4), including social determinants of health and well-being. Multiple linear regression, logistic regression, and random forests (RF) were used to explore predictors of MIBS-4. Results The majority of participants (90%) were female with a mean (standard deviation) age of 40.6 (± 12.0) years and 18.1 (± 12.7) years since the first migraine episode. Sociodemographically, the EM and CM groups were similar. Common comorbidities were anxiety disorder (45%) and depression (44%). Migraine family history was reported in 59% of participants. MIBS-4 was correlated with a number of diverse variables, including well-being, anxiety sensitivity, income, aura symptoms, and the worst migraine pain in the year before starting galcanezumab. Linear and logistic regression identified years since the first symptom, worst migraine attack pain, premonitory symptoms, and income as significant predictors. RF explained more of the variance than multiple linear regression and introduced additional concepts to the prediction of MIBS, identifying well-being (WHO-5 total score), the WHO-5 item “cheerful and in good spirits,” worry about exercise, and fear of missing social obligations as significant predictors. Socioeconomic status and income were also critical explanatory variables for interictal burden (IIB) based on regression modeling and RF. Still, income was the only variable significantly associated with IIB across regression and RF methods. Conclusions Interictal burden should be considered in the medical care of people with migraine. This additional burden is holistic, with psychosocial and socioeconomic elements in addition to residual symptoms. It is essential to consider this when assessing the impact of IIB.